Career optimism of Jakarta’s University students - Br Colia, Ria Febrina; Gunawan, William (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2025)
Career optimism is an important factor that influences university students’ readiness to face the world of work. Given the significant challenges posed by career uncertainty today, understanding university students’ levels of career optimism is an important area of investigation. This study aims to examine the level of career optimism among university students in Jakarta.  A descriptive quantitative approach was employed involving 866 active students from several higher education institutions in Jakarta. The measurement instrument used was the Career Futures Inventory (CFI), particularly the Career Optimism sub-scale, which had been translated into Indonesian. Data analysis was carried out by using descriptive statistical techniques. The instrument achieved acceptable construct validity, evidenced by item–total correlations (r ≥ 0,30), and demonstrated high reliability with a Cronbach’s alpha of 0,85, making it appropriate for use in this research. The study revealed that the majority of university students were classified as having high (37,8%) and moderate (29,8%) levels of career optimism, indicating that they hold positive views about their prospective careers. These findings emphasize the need for comprehensive career support within higher education institutions to improve students’ readiness for employment. Additionally, the study provides groundwork for implementing campus-level psychological interventions targeting improvements in students’ confidence, career self-efficacy, and early comprehension of world of work conditions.